2015
DOI: 10.1111/jmft.12140
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Solution‐Focused Versus Problem‐Focused Questions: A Replication

Abstract: In therapeutic conversations, questions can be considered as interventions in their own right. This study is a cross-cultural replication of Grant (Journal of Systemic Therapies, 2012, 31, 2, 21) study on the effects of different types of questions on various clinically relevant variables. A total of 204 students of a Spanish university described a real-life problem that they wanted to solve and were then randomly assigned to either a solution-focused or a problem-focused questions condition. Before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 33 publications
4
24
1
Order By: Relevance
“…perceived closeness to solving one's problem). A follow-up study by Grant (2012) replicated these findings in a randomised, experimental design using Australian participants, and Neipp, Beyebach, Nuñez, and Martínez-González (2015) replicated those findings in a Spanish student population.…”
Section: Coaching Orientations: Sf Approachessupporting
confidence: 74%
See 1 more Smart Citation
“…perceived closeness to solving one's problem). A follow-up study by Grant (2012) replicated these findings in a randomised, experimental design using Australian participants, and Neipp, Beyebach, Nuñez, and Martínez-González (2015) replicated those findings in a Spanish student population.…”
Section: Coaching Orientations: Sf Approachessupporting
confidence: 74%
“…Overall, the current findings make an important contribution to the emerging empirical evidence base for the effectiveness of SF coaching questions, replicating and extending previous research by Grant and O'Connor (2010), Grant (2012), Theeboom et al (2015) and Neipp et al (2015). This is an important point given the high level of current concern about the lack of replication of findings in psychology (Bohannon, 2015), and this is one area where such research can make a contribution to the broader psychological enterprise.…”
Section: Sf Vs Pf Coaching Questionssupporting
confidence: 61%
“…In a cross-cultural replication using the same procedure, variables and measures, Neipp et al (2016) also found that SF questions were more effective than PF counterparts in enhancing perceived self-efficacy and goal approach and in reducing negative affect. Effect size estimates were again not provided by the authors but these can be calculated using their data.…”
Section: Background and Prior Researchmentioning
confidence: 73%
“…Hosseinpour et al (2016) determined that solution-focused thinking is effective in individuals adapting to various situations. Neipp et al (2015) found an increase in university students' positive affection, selfefficacy, and ability to reach their goals after answering solution-focused questions.…”
Section: Discussionmentioning
confidence: 89%